2016
DOI: 10.1038/srep22474
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-involved mechanisms in enhancing systemic exposure of ginsenosides by coexisting polysaccharides in ginseng decoction

Abstract: Oral decoctions of traditional Chinese medicines (TCMs) serve for therapeutic and prophylactic management of diseases for centuries. Small molecules and polysaccharides are the dominant chemicals co-occurred in the TCM decoction. Small molecules are well-studied by multidisciplinary elaborations, whereas the role of polysaccharides remains largely elusive. Here we explore a gut microbiota-involved mechanism by which TCM polysaccharides restore the homeostasis of gut microbiota and consequently promote the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 59 publications
5
98
0
Order By: Relevance
“…It has been found that unlike Bacteroidetes, Firmicutes and Actinobacteria express very few carbohydrate-degrading enzymes but enriched with polysaccharide-specific ABC (ATP-binding cassette) transporters which play an important role in the transportation of degraded carbohydrates [69]. This might largely account for the variation of phylum Firmicutes and Actinobacteria in response to the treatment with ginseng polysaccharides as revealed in a previous study [70]. …”
Section: Discussionmentioning
confidence: 96%
“…It has been found that unlike Bacteroidetes, Firmicutes and Actinobacteria express very few carbohydrate-degrading enzymes but enriched with polysaccharide-specific ABC (ATP-binding cassette) transporters which play an important role in the transportation of degraded carbohydrates [69]. This might largely account for the variation of phylum Firmicutes and Actinobacteria in response to the treatment with ginseng polysaccharides as revealed in a previous study [70]. …”
Section: Discussionmentioning
confidence: 96%
“…If further substantiated and characterized, this area could have a significant impact both on prophylaxis as well as on treatment of cancer. It is also tempting to speculate that oral decoctions in traditional Chinese medicine specifically target the hologenome [7880], but further studies are necessary to clarify this point.…”
Section: Big Data and Clinically Useful Knowledgementioning
confidence: 99%
“…With the character of complex composition, ginseng usually acts on multireceptor systems or non-target impacts such as intestinal microbiota15. Thus, we need seek for integrative approach to deepen pharmacology mechanism.…”
mentioning
confidence: 99%